Ahammiyah al-Tazkiyyah fī Tarbiyyah al-Insān min Khilāl al-Ru’yah al-Ḥaḍāriyyah al-Islāmiyyah: Significance of Purification in Human Education According to Islamic Civilisational Vision - Berghout, Abdelaziz (Jurnal Usuluddin, 2020)
This paper analyses the importance of purification (Tazkia) and its place in bringing up balanced man in light of the integrated Islamic civilizational vision. It focuses on various dimensions and meanings of Tazkia relating it to the concept of vicegerency (Istikhlaf) and its objectives of worship, civilisational advancement, ethical excellence and conveying the message of â€œmercy to all mankindâ€. The Islamic sources and evidences have vehemently shown the importance of Islamic oriented model of Tazkia in educating man, strengthening society and protecting the major values of Islam. Hence, this paper aspires towards addressing the meaning of Tazkia connecting it to several other concepts and Islamic principles such as; Tawhid, vicegerency, civilisation and Ummah. The paper concludes that there is a need to develop more coherent and integrated vision to use Tazkia as an educational, spiritual and ethical means to build good vicegerent of God. As such, an attempt has been made to shed some lights on this vision urging others researchers to delve onto this important area of Islamic research. This paper also stresses the need to revisit the methods and approaches of Tazkia in order to renew them according the Islamic teachings. Furthermore, the paper recommends the re-activation of the roles of educational, cultural, religious, social and intellectual institutions in advancing the moderate approaches of Tazkia according to the standards and values â€‹â€‹of Islamic worldview. Finally, the paper suggests more in-depth studies on the social, behavioral, ethical, spiritual and intellectual impacts and applications of Tazkia in our life.